Evaluation of Postgraduate Surgical Educational Environment - ShaziaZeb,RizwanaShahid ,TariqMasoodKhan (Journal of Rawalpindi Medical College, 2016)
Background: To evaluate the educational climate of postgraduate trainees working in surgical departments Methods: In this cross-sectional descriptive study 77 postgraduate trainees were enrolled. The data was collected by using internationally validated Postgraduate Hospital Educational Environment Measure (PHEEM), questionnaire . PHEEM is a 40 item questionnaire that comprises of 3 broad components. These components are meant to perceive the role autonomy of postgraduate residents, their teaching during their training in hospitals and social support available to them during training. Each item of PHEEM questionnaire scores 0-4 on 5 point likert scale. Maximum score is 160. Data was analyzed using SPSS version 16. Mean and standard deviation were calculated for each item. Moreover, percentage and frequency were also depicted during inter hospital and inter departmental comparisons. Results: On PHEEM analysis, total score was calculated to be 130.32±48.34. 81.4% trainees were contented with the autonomy available to them during training while 88.4% were comfortable with teaching opportunities offered during training. However, social support provided to them was affirmed to be 72.1%. Conclusion: Overall learning environment of clinical trainees was satisfactory particularly regarding their clinical teaching and provision of autonomy to them in their respective units. However social support should be further augmented to maximize their learning.